Zapisz wyrażenie w najprostszej postaci.(Obliczenia rozpisane)

a) (a²-3a+2)+(a²-4a+5)=
b) (a²-3a+2)-(a²-4a-2)=
c)(a-3)+(7-2a)-(a+4)=
d)-(2a³+5a-3)-(-a³-a)+(a³-2a+4)=
e)(x-y)+(x+2y)=
f)(2x+8)+(x-5)=
g)(x²-2+4)+(x²+2x-1)=
h)(3xy-2x+4y)+(-5xy+7x-4y)=

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-07T14:40:32+01:00
A) (a²-3a+2)+(a²-4a+5)=a²-3a+2+a²-4a+5 =2a²-7a+7
b) (a²-3a+2)-(a²-4a-2)=a²-3a+2-a²+4a+2=a+4
c)(a-3)+(7-2a)-(a+4)=a-3+7-2a-a-4=-2a
d)-(2a³+5a-3)-(-a³-a)+(a³-2a+4)=-2a³-5a+3+a³-a=a³-6a+3
e)(x-y)+(x+2y)=x-y+x+2y=2x+y
f)(2x+8)+(x-5)=2x+8+x-5=3x+3
g)(x²-2+4)+(x²+2x-1)=x²-2+4+x²+2x-1=2x²+1+2x
h)(3xy-2x+4y)+(-5xy+7x-4y)=3xy-2x+4y+(-5xy)+7x-4y=-2xy+5x
1 5 1
2010-03-07T14:41:49+01:00

a) (a²-3a+2)+(a²-4a+5)=a²-3a+2+a²-4a+5=2a²-7a+7
b) (a²-3a+2)-(a²-4a-2)=a²-3a+2-a²+4a+2=a+4
c)(a-3)+(7-2a)-(a+4)=a-3+7-2a-a-4=-2a
d)-(2a³+5a-3)-(-a³-a)+(a³-2a+4)=-2a³-5a+3+a³+a+a³-2a+4=-6a+7
e)(x-y)+(x+2y)=x-y+x+2y=2x+y
f)(2x+8)+(x-5)=2x+8+x-5=3x+3
g)(x²-2+4)+(x²+2x-1)=x²-2+4+x²+2x-1=2x²+1+2x
h)(3xy-2x+4y)+(-5xy+7x-4y) =3xy-2x+4y+-5xy+7x-4y=-2xy+5x
1 5 1
2010-03-07T14:43:32+01:00

a) (a²-3a+2)+(a²-4a+5)=
a²-3a+2+a²-4a+5=
2a²-7a+7
b) (a²-3a+2)-(a²-4a-2)=
a²-3a+2-a²+4a+2=
a+4
c)(a-3)+(7-2a)-(a+4)=
a-3+7-2a-a-4=-2a
d)-(2a³+5a-3)-(-a³-a)+(a³-2a+4)=
-2a³-5a+3+a+a+a³-2a+4=
-a³-5a+7
e)(x-y)+(x+2y)=
x-y+x+2y=2x+y
f)(2x+8)+(x-5)=
2x+8+x-5=3x+3
g)(x²-2+4)+(x²+2x-1)=
x²-2+4+x²+2x-1=
2x²+2x+1
h)(3xy-2x+4y)+(-5xy+7x-4y) =
3xy-2x+4y+(-5xy)+7x-4y=
5x-2xy
1 5 1